2016
DOI: 10.1186/s40410-016-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for prospect-refuge theory: a meta-analysis of the findings of environmental preference research

Abstract: Background: Researchers in the field of spatial psychology and environmental preference theory have tested a range of claims about the capacity of certain spatial configurations to evoke a positive sense of wellbeing in observers. In parallel, across the landscape, urban, architectural and interior design disciplines, there has been a growing acceptance that a balance of spatial characteristics-including prospect, refuge, mystery and complexity-is desirable in a natural, urban or interior environment. Yet, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 29 publications
4
48
0
3
Order By: Relevance
“…Salingaros suggested that buildings stripped of visual complexity, like prisons, deny the information-seeking visual system access to meaningful information (Salingaros, 2003). Empirical findings tentatively support this view, suggesting that people generally prefer at least a moderate level of visual complexity when viewing both art and architectural interiors (Dosen & Ostwald, 2016;Leder et al, 2004;Frith & Nias, 1974). As Berlyne postulated many years ago, preferences tend to follow an inverted U-shaped curve in relation to complexity (Güçlütürk, Jacobs, & van Lier, 2016;Imamoglu, 2000;Berlyne, 1970Berlyne, , 1971.…”
Section: Visionsupporting
confidence: 59%
See 2 more Smart Citations
“…Salingaros suggested that buildings stripped of visual complexity, like prisons, deny the information-seeking visual system access to meaningful information (Salingaros, 2003). Empirical findings tentatively support this view, suggesting that people generally prefer at least a moderate level of visual complexity when viewing both art and architectural interiors (Dosen & Ostwald, 2016;Leder et al, 2004;Frith & Nias, 1974). As Berlyne postulated many years ago, preferences tend to follow an inverted U-shaped curve in relation to complexity (Güçlütürk, Jacobs, & van Lier, 2016;Imamoglu, 2000;Berlyne, 1970Berlyne, , 1971.…”
Section: Visionsupporting
confidence: 59%
“…The frequent patches of trees scattered throughout the savannah ( Joye, 2007) likely offered early hominids places to hide from predators and survey the plains in search of resources, mates, and prey (Appleton, 1975). A review by Dosen and Ostwald indicates that both prospect (a clear view of the environment) and refuge (safe places to hide) predict visual preferences for natural settings and that these preferences also extend to built environments (Dosen & Ostwald, 2016). People often prefer architectural interiors and urban spaces that are more open and visually connected to their surroundings compared with enclosed environments (Dosen & Ostwald, 2016).…”
Section: Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment guided early humans or human ancestors to perceive and recognize landscape features as they traversed savannas that could be hazards, places of safety as well as resources, friends, foes, potential mates (Appleton, 1996; Hildebrand, 1999). In support of this theory, behavioral studies have generally demonstrated a human preference for prospect and refuge in both exterior and interior environments, as analyzed by Dosen and Ostwald (2013, 2016), which may be supported by specific sensorimotor networks in the brain (Di Dio et al, 2016). Moreover, prospect-refuge theory posits that prospect and refuge are mutually interdependent and much of what is so tacitly attractive about Frank Lloyd Wright’s house designs is said to be their affordance of both prospect and refuge (Hildebrand, 1999).…”
Section: Exploring Neural Constraints On Urban Formmentioning
confidence: 92%
“…The effect of visible sky and green cover has been studied explicitly in preference-based studies as it had been a prime constituent of assessment of the variables such as prospect and refuge [59]. The feelings of safety and pleasure are derived from surroundings providing a sense of enclosure and views [60]. Studies such as [13] have created tools to analyse the sky-green ratios for cities, which help urban planners to explore urban areas with interactive visual analysis.…”
Section: Visible Sky and Greenmentioning
confidence: 99%